Pengaruh Persepsi Dukungan Organisasi dan Keterikatan Kerja Terhadap Organizational Citizenship Behavior (OCB) Peran Mediasi Kepuasan Kerja Pada Pegawai Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Rokan Hulu - Amdanata, Donal; Yusanrinofitri, Yusanrinofitri; Oemar, Fahmi (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2024)
The purpose of this study was to determine the effect of Perceived Organizational Support and work engagement on Organizational citizenship behavior (OCB) with job satisfaction as a mediating variable. The population in this study were ASN Employees at the Investment Service and One-Stop Integrated Services of Rokan Hulu Regency, totaling 92 people with details of 44 ASN people and 48 honorary people, where the sample was taken using the saturated sample method. Data collection techniques using questionnaires and dissemination using Google Forms. The data analysis technique in this study was Structural Equation Modeling (SEM) using SmartPLS 3.0 as a data processing tool. The results of this study indicate that work engagement and job satisfaction have a direct significant effect on OCB of ASN employees at the Investment Service and One-Stop Integrated Services in Rokan Hulu Regency. However, Perceptions of Organizational Support do not have a significant effect on OCB of ASN employees at the Investment and One-Stop Services Office of Rokan Hulu Regency. The results of the study also show that job satisfaction is able to mediate the relationship between perceptions of organizational support and work engagement on OCB of ASN employees at the Investment Service and One Stop Integrated Services, Rokan Hulu Regency.